Enhanced heavy metal leaching from sewage sludge through anaerobic fermentation and air-assisted ultrasonication - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ; YEŞİL, HATİCE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Interest in using stabilized sewage sludge in agriculture is mainly to benefit from its nutrient content, soil conditioning properties, and water holding capacity. Therefore, sludge management practice needs to be directed from treatment liability towards the recovery of chemical assets embedded in sludge. In this study, anaerobic fermentation process integrated with a new treatment method; i.e., air-assisted ultra-sonication, was used to assess the leaching of heavy metals (HM) from waste activated sludge (WAS). Fermentation processes resulted in 9390 mg COD/L of volatile fatty acids (VFAs) production, 26% Ni solubilization and up to 3.4% solubilization of other target metals (Cu and Zn). Application of the air-assisted ultrasonication as a post-treatment to fermentation process stimulated the migration and transformation of HMs to the liquid fraction of the digestate. Applying specific energy input greater than 9 kJ/g total solids (TS) through ultrasonication and supplying air with constant flow rate of 0.875 L of air/(L of digestate.min) resulted in leaching of more than 83% of Ni, 82% of Cu and 80% of Zn. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Anaerobic bioleaching; Heavy metal; Post-treatment; Sewage sludge; Volatile fatty acids; WASTE ACTIVATED-SLUDGE; EXTRACELLULAR POLYMERIC SUBSTANCES; SEQUENTIAL EXTRACTION; METHANE PRODUCTION; CO-DIGESTION; WATER SLUDGE; PRETREATMENT; REMOVAL; ACID; DISINTEGRATION